EKO PESANTREN: MEWUJUDKAN PESANTREN PEDULI DAN BERBUDAYA LINGKUNGAN BERBASIS KEMANDIRIAN - Suryanto, Bradhiansyah Tri (JURNAL ISLAM NUSANTARA, 2019)
This research presents about the efforts of pesantren in realizing caring and cultured students of the environment based on the independence of pesantren, with a research site at Pondok Pesantren Nurul Jadid, Paiton, Probolinggo. As a pesantren which has considerable potential in santri in making changes and renewals, especially related to the creation of a friendly and comfortable environment, it is one of the very potential media in overcoming the current and future environmental crises. Given the many behaviors that indicate the lack of environmental awareness shown by society today. This research uses a qualitative approach with case study. The results showed; the efforts of Pondok Pesantren Nurul Jadid Paiton Probolinggo in realizing caring and cultured environmental students based on independence, namely; development of environment-based curriculum, foster theological awareness about the importance of caring for the environment, development of participatory-based environmental activities.